(untitled) (Medico Legal Update, 2020)
Decubitus ulcer event is an indicator of patient safety in nursing care at the clinic, so a method is needed to reduce the incidence of decubitus ulcer in the patient in hospital. The research aims to create a model for increasing patient safety based on Organizational Citizenship Behavior (OCB) and knowledge management on unexpected events (decubitus ulcer) in achieving the target of patient safety program in Hospital, using cross-sectional design. The subjects were 100 nurses who work in the inpatient room of Surabaya Haji Hospital, selected by purposive sampling. Data collection was done by questionnaire, then analyzed using Partial Least Square (PLS). The model of increasing patient safety based on OCB and knowledge management has proven effective in reducing the incidence of decubitus ulcer in the patient ward. This model is recommended to implement in the hospital to enhance the quality of nursing care.